Measurement of Countable Compactness and Lindelöf Property in RL-Fuzzy Topological Spaces - Xiongwei Zhang; Ibtesam Alshammari; A. Ghareeb (Complexity)
Based on the concepts of pseudocomplement of L-subsets and the implication operator where L is a completely distributive lattice with order-reversing involution, the definition of countable RL-fuzzy compactness degree and the Lindelöf property degree of an L-subset in RL-fuzzy topology are introduced and characterized. Since L-fuzzy topology in the sense of Kubiak and Šostak is a special case of RL-fuzzy topology, the degrees of RL-fuzzy compactness and the Lindelöf property are generalizations of the corresponding degrees in L-fuzzy topology.